An investigation into the factors influencing travel needs during later life. (December 2018) - Luiu, Carlo; Tight, Miles; Burrow, Michael
Abstract: As the population in Western countries becomes older, providing transportation able to meet travel needs during later life will become more challenging, especially due to the heterogeneity and differences in background, health and travel patterns of that population. Given the importance of the link between the ability to be mobile and use transportation with individuals' wellbeing, this study investigates the factors which influence the fulfilment of travel needs amongst the older population. The study employs a conceptual framework based on five interrelated domains that shape and influence out-of-home travel needs during later life. The results indicate that access to the car, especially as a driver, and individuals' health and wellbeing conditions are the two main factors affecting the fulfilment of travel needs with regards to both realised mobility and unmet travel needs. Around one-third of the respondents reported the need to undertake more out-of-home activities than they do, particularly older women. Activities reported more in this sense were those related to the discretionary domain such as visiting other people and undertaking social and leisure activities. Highlights: This study explores the factors influencing travel needs' fulfilment amongst older people. The study employs a framework that is a construct of five interrelated domains shaping mobility in later life. The results indicate that car access and health are the two main factors affecting travel needs. One-third of respondents reported unmet travel needs, particularly older women. Social/leisure activities and visiting other people were reported to be the activities most unfulfilled.